Removal of pharmaceuticals by vertical flow constructed wetland with different configurations: Effect of inlet load and biochar addition in the substrate. (November 2022) - Chand, Naveen; Suthar, Surindra; Kumar, Kapil; Singh, Vineet
Abstract: Pharmaceuticals (PCs) residues are considered an emerging threat to the environment due to their persistency, ecotoxicity and bioaccumulative nature. To study the PC (amoxicillin, AMX; caffeine, CF; ibuprofen, IBU) removal efficiency of vertical flow constructed wetland (VFCW), three setups of VFCWs were configured: SB (substrate matrix + biochar (BC)); SBP (substrate matrix + BC + plant); SP (substrate matrix + plant) and changes in effluent PC load was estimated at 24, 48, 72, 96, 120, 144 and 168 h intervals. SBP with an influent load of 1, 000 μg L −1 showed the maximum removals of 75.51% (AMX), 87.53% (CF), and 79.93% (IBU) significantly higher than that of SB and SP ( p  < 0.00). Results showed an inverse relationship between removal efficacy and influent PCs loading. The average removal (%) by VFCWS (of all studied setups) was in the order: 66.20 > 47.88 > 39.0 (IBU), 56.56 > 42.12 > 34.36 (AMX), and 74.13 > 64.0 > 52.07 (CF) with 1, 000, 5, 000 > 10, 000 μg L −1 influent load, respectively. The maximum removal of COD, NH4 + -N, and NO3 –N was recorded at 88.8%, 83.1%, and 64.9%, respectively in SBP, and their removal was hardly affected by influent PC concentration. In summary, planted VFCW spiked with BC could be a viable approach for the removal of PCs in wastewater. The impact of PC load on plant toxicity in VFCWs can be taken as a research problem for future work in this series. Graphical abstract: Image 1 Highlights: Biochar-aided VFCW showed high removal of caffeine, ibuprofen and amoxicillin. Plant stand Colocasia played a vital role in the degradation of PCs. The high influent load of PCs affected the removal rates in VFCWs inversely. COD, NH4 + -N, and NO3 –N removals interrelated with PC influent load.